2020
DOI: 10.1002/jbmr.4033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biochemical Remission on Bone Metabolism in Cushing's Syndrome: A 2-Year Follow-Up Study

Abstract: Endogenous Cushing's syndrome (CS) is a rare cause of secondary osteoporosis. The long‐term consequences for bone metabolism after successful surgical treatment remain largely unknown. We assessed bone mineral density and fracture rates in 89 patients with confirmed Cushing's syndrome at the time of diagnosis and 2 years after successful tumor resection. We determined five bone turnover markers at the time of diagnosis, 1 and 2 years postoperatively. The bone turnover markers osteocalcin, intact procollagen‐IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…In CS-MET group, 9 out of 10 patients continued metformin therapy until one-year follow-up. For the comparison of bone remodeling markers, a previously described registry control group of patients in whom CS was excluded (NO-CS group, n=95) was used ( 14 ). The German Cushing’s Registry (NeoExNet, No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In CS-MET group, 9 out of 10 patients continued metformin therapy until one-year follow-up. For the comparison of bone remodeling markers, a previously described registry control group of patients in whom CS was excluded (NO-CS group, n=95) was used ( 14 ). The German Cushing’s Registry (NeoExNet, No.…”
Section: Methodsmentioning
confidence: 99%
“…This cohort study was performed as part of the German Cushing's Registry. General characteristics of the registry have been described in detail previously (12)(13)(14). We screened the prospective registry cohort consisting of 96 patients with endogenous CS for metformin intake at the time of diagnosis.…”
Section: Patientsmentioning
confidence: 99%
“…Cushing’s syndrome (CS) results from chronic exposure to either endogenous or exogenous excess of cortisol ( 1 ). A well-known complication of hypercortisolism in CS is glucocorticoid-induced osteoporosis (GOP) ( 2 , 3 ). GOP is thought to be the result of a combination of decreased intestinal calcium absorption and renal calcium resorption, increased bone resorption, decreased bone formation and muscle wasting.…”
Section: Introductionmentioning
confidence: 99%
“…GOP is thought to be the result of a combination of decreased intestinal calcium absorption and renal calcium resorption, increased bone resorption, decreased bone formation and muscle wasting. Consequently, biochemical remission of Cushing’s syndrome results in an increase in bone mineral density ( 3 ). Recently, it has been suggested that treatment with glucocorticoids could also affect phosphate homeostasis and even induce hypophosphatemia due to increased urinary phosphate excretion ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, we appreciate the great interest of Dutta and colleagues in our work. (1) We provide a few comments and clarifications.…”
mentioning
confidence: 99%